Crowding out the freight handling of the city centers during economic boost - Viggo Jean-Hansen (European Regional Science Association (ERSA), 2010)
Norwegian cities are small in a European context. But even in these medium sized cities one finds that the crowding out process during economic growth works out the way economic theory prescribes. In years where there is high economic growth the land rent tends to increase. This should suffice that the high value industries will have a higher demand for offices and activities close to the city centre. More labor is needed in the city both by the public and the private sector. But the new employment will be pushed out to the outskirts of the city. As the rent increases the shops selling cheap goods tend to be established outside the city centre as the rent for land increase. Freight transport activities serve the shopping malls and the wholesalers in the outskirts of the city. Freight activities become less frequent in the city centre during a boom. Does one find economic empirical data to support this? We have divided the three biggest cities in Norway (Oslo, Bergen and Trondheim) in one central part and one part for the rest of the city. We have looked at employment data for years from 2002 to 2007 for the parts of the cities. In Norway there was a slump in the economy in the beginning of decennium up to 2003. The following years (2004 - 2007) there were a boom in the Norwegian mainland economy. In this paper we have investigated the localization pattern of industries in the three cities. We have looked at which industries are the best survivors during the period of high economic growth in the cities. According to economic theory it is supposed that activities that need more space (as supermarkets and warehouses) will be forced out, but real estate agents and other business services will survive in the spatial competition in the center of the city. Our employment data for the three cities supports the theory. Industries with lower wages per employed are crowded out of the centre during the boom while the service sectors are moving in.
Keywords: 330